2014
DOI: 10.1161/strokeaha.114.007058
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Synchronous Verbal Training During Repetitive Transcranial Magnetic Stimulation in Patients With Chronic Aphasia

Abstract: Background and Purpose-Although multiple studies have suggested that repetitive transcranial magnetic stimulation (rTMS) may facilitate recovery after stroke, the efficacy of synchronous speech therapy integrated with an rTMS protocol has yet to be determined. We investigated language responses to this strategy and determined the longevity of the resulting therapeutic outcomes. Methods-Forty-five patients with stroke who presented with nonfluent aphasia were randomly assigned to the TMS syn group and underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 26 publications
2
64
0
2
Order By: Relevance
“…[ 9 , 10 ] Furthermore, SLT was a constant condition, which would consolidate the changes. [ 11 ] Moreover, the patient was more willing to communicate with other individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 , 10 ] Furthermore, SLT was a constant condition, which would consolidate the changes. [ 11 ] Moreover, the patient was more willing to communicate with other individuals.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] Researchers have shown that rTMS has a long-term efficacy, [ 9 , 10 ] and rTMS together with SLT, they can consolidate the efficacy. [ 11 ] In this study, we hypothesized that rTMS combined with rehabilitation training would be more beneficial for the functional recovery of language in aphasic patients. [ 12 , 13 ] However, the neural mechanisms of the functional recovery of language post-TMS combined with rehabilitation training in aphasia remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The special feature of this trial is its focus on attainment of a predefined, participation-related goal relevant to everyday life and its verification of goal attainment in the real home environment. There have already been multiple clinical studies of rehabilitation showing that specific measures can attain functional and activity-related improvements even in chronic patients, such as constraint-induced movement therapy for arm and hand function (22), robotic arm and hand training (23-25), task-specific arm and hand training (26), and intensive speech therapy combined with transcranial magnetic stimulation (27). However, many of these studies were not controlled or used only very small case numbers, and patients' individual living environments were not taken into account when their results were measured.…”
Section: Discussionmentioning
confidence: 99%
“…Im chronischen Stadium nach Schlaganfall fokussieren sich die in den letzten Jahren publizierten Studien v. a. auf die rTMS Behandlung von Patienten mit expressiven Aphasien [95][96][97][98]. Während eine Studie zeigen konnten, dass ein 10-tägiges 1Hz-rTMS-Protokoll (600 Pulse, 80 % RMT) über dem rechten IFG zu einer Verbesserung der Aphasie gegenüber einer gleichartig applizierten 10 Hz-Stimulation führen kann und diese Effekte auch noch nach 2 Monaten nachweisbar sind [96], demonstrierten 2 weitere Studien, dass 1Hz-rTMS (600 bzw.…”
Section: Rtmsunclassified